2020
DOI: 10.1080/02770903.2020.1723623
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab add-on therapy in a real world cohort of patients with severe eosinophilic asthma: response rate, effectiveness, and safety

Abstract: Introduction: Severe eosinophilic asthma is an incapacitating disease. Mepolizumab, a humanized anti-interleukin-5 monoclonal antibody, proved to be effective as an add-on therapy in patients with severe eosinophilic asthma. However, only data from randomized controlled trials are available and real world data are lacking. Methods: A retrospective observational longitudinal study was conducted in a real world cohort of patients with severe eosinophilic asthma treated with mepolizumab. The primary objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Severe asthma exacerbations per year were significantly reduced after 12 months of treatment accompanied by a reduction of 0.80 points in ACQ, and an increase in FEV 1 compared to baseline. A reduction in OCS usage was also observed (51.3% at baseline vs. 15.4%), 12 months after drug initiation and importantly, no serious adverse events related to mepolizumab treatment were reported [27]. Similar findings come from a retrospective study of 138 patients treated with mepolizumab for at least 12 months in Italy where mepolizumab confirmed its effectiveness in significantly reducing exacerbation rates and OCS usage, thus replicating the efficacy and safety profile shown in RCTs [28].…”
Section: Mepolizumabsupporting
confidence: 69%
“…Severe asthma exacerbations per year were significantly reduced after 12 months of treatment accompanied by a reduction of 0.80 points in ACQ, and an increase in FEV 1 compared to baseline. A reduction in OCS usage was also observed (51.3% at baseline vs. 15.4%), 12 months after drug initiation and importantly, no serious adverse events related to mepolizumab treatment were reported [27]. Similar findings come from a retrospective study of 138 patients treated with mepolizumab for at least 12 months in Italy where mepolizumab confirmed its effectiveness in significantly reducing exacerbation rates and OCS usage, thus replicating the efficacy and safety profile shown in RCTs [28].…”
Section: Mepolizumabsupporting
confidence: 69%
“…In randomized clinical trials (RCT), mepolizumab has been demonstrated to produce a significant reduction in exacerbations and steroid intake and to improve asthma control in patients with a peripheral eosinophil count >300 cell/mm 3 [9, 10]. These results have also been reported in real-world studies, confirming the cost-effectiveness and good safety profile of the drug [11, 12].…”
Section: Introductionmentioning
confidence: 79%
“…In severe persistent eosinophilic asthma, the percentage of patients that received daily OCS dropped from 76% before starting mepolizumab treatment to 12% after 1 year of treatment [54]. Additionally, in the study of van Toor et al [58], the percentage of patients requiring OCS was reduced to 15.4% after 1 year of treatment with mepolizumab. The predesigned interim analysis of a 2-year study [53] reported that in patients who completed 1 year of therapy with mepolizumab, a 56% reduction in the dose of OCS was achieved, from 10.1 mg/day to 4.5 mg/day.…”
Section: Mepolizumabmentioning
confidence: 97%
“…Of the 1757 potentially relevant records identified in the initial search, 59 real-world studies were deemed eligible for a qualitative analysis. Six studies were carried out on benralizumab [34][35][36][37][38][39], 1 on dupilumab [40], 18 on mepolizumab [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 27 on omalizumab [18,, and 3 on reslizumab [85][86][87]. Four studies investigated different mAbs in the same report [88][89][90][91].…”
Section: Study Characteristicsmentioning
confidence: 99%